Adsorption sensitivity of graphane decorated with B, N, S, and Al towards HCN: a first-principles study. Issue 69 (8th September 2017) - Zhou, Qingxiao; Ju, Weiwei; Su, Xiangying; Yong, Yongliang; Li, Xiaohong; Fu, Zhibing; Wang, Chaoyang
Abstract : The geometric structure, adsorption energy, electronic structure, and magnetic properties of hydrogenated graphene (graphane) with the adsorption of a HCN molecule were investigated by first-principles calculations. Abstract : The geometric structure, adsorption energy, electronic structure, and magnetic properties of hydrogenated graphene (graphane) with the adsorption of a HCN molecule were investigated by first-principles calculations. Compared with graphane, the adsorption of HCN on H-vacancy defected graphane (VHG) exhibited higher stability, which implied that the H-vacancy improved the sensitivity of graphane. However, the small adsorption energies and large bond distance indicated that the weak adsorption of a HCN molecule on the graphane and VHG substrates was due to physisorption. By introducing dopants (B, N, S, and Al), the activity of graphane was significantly improved. The adsorption of HCN changed to chemisorption on the graphane with dopants. Meanwhile, the opening of band gaps by HCN adsorption can be used as an electronic signal to detect HCN gas. Interestingly, the spin polarized density of states (PDOS) results suggested that the adsorption of HCN on VHG and S-doped VHG exhibited magnetic character and half-metallicity behavior. These results could provide useful information to design gas sensors for HCN or spintronic devices based on graphane.